Repurposing antitussive benproperine phosphate against pancreatic cancer depends on autophagy arrest. Issue 2 (12th December 2020) - Zhang, Huanyu; Zhang, Zhe; Huang, Yonghao; Qin, Siyuan; Zhou, Li; Weng, Ningna; Liu, Jiayang; Yang, Mei; Zhang, Xiaodian; Lu, Yanda; Ma, Lin; Zheng, Shaojiang; et al.
Abstract : Pancreatic cancer (PC) is one of the most common human malignancies worldwide and remains a major clinical challenge. Here, we found that benproperine phosphate (BPP), a cough suppressant, showed a significant anticancer effect on PC both in vitro and in vivo via the induction of autophagy‐mediated cell death. Mechanistic studies revealed that BPP triggered AMPK/mTOR‐mediated autophagy initiation and disturbed Ras‐related protein Rab‐11A (RAB11A)‐mediated autophagosome–lysosome fusion, resulting in excessive accumulation of autophagosomes. Inhibition of autophagy or overexpression of RAB11A partially reversed BPP‐induced growth inhibition in PC cells, suggesting that BPP might induce lethal autophagy arrest in PC cells. In conclusion, our results identify BPP as a potent antitumor agent for PC via the induction of autophagy arrest, therefore providing a new potential therapeutic strategy for the treatment of PC. Abstract : Here, we show that benproperine phosphate (BPP), a cough suppressant, triggers AMPK/mTOR‐mediated autophagy initiation and disturbs Ras‐related protein Rab‐11A (RAB11A)‐mediated autophagosome–lysosome fusion, resulting in excessive accumulation of autophagosomes in pancreatic cancer (PC) cells. Inhibition of autophagy or overexpression of RAB11A partially reverses BPP‐induced growth inhibition in PC cells, suggesting BPP as a potent anti‐PC agent via the induction of autophagy arrest.